Power quality investigation of CHB nine‐level converter based large‐scale solar PV system with different modulation schemes - Jyoti Kulkarni; Shivam Kumar Yadav; Bhim Singh; Narendra Kumar (Energy Conversion and Economics, 2021)
Abstract Multilevel converters (MLCs) are extensively used in solar photovoltaic (SPV) applications owing to their advantages such as low total harmonic distortion (THD) in the converter voltage, reduction in device stress, and switching losses. A suitable modulation technique is important for the efficient closed‐loop control of megawatt (MW)‐scale solar photovoltaic plants. This work utilises different modulation techniques, such as phase‐shifted (PS) multicarrier pulse width modulation (PWM), selected harmonic elimination (SHE), and nearest level modulation (NLM), for switching of cascaded H‐bridge (CHB) converter‐based large‐scale SPV systems. The investigation on improving power quality is presented with a suitable fast Fourier transform (FFT) analysis and comparative graphs. The presented control and modulation enhance the power quality of the output current being fed to the grid in the dynamic solar profile. Moreover, the low switching frequency employed in this photovoltaic converter at a high power rating increases the system efficiency. Graphical illustrations of losses with fundamental and PWM switching were analysed for the MW‐rated system. The obtained results show that SHE‐PWM provides the best performance for large‐scale solar power plants. Furthermore, the IEEE‐519 standard was met for both grid voltages and currents. The system was modelled and simulated in MATLAB/Simulink and validated in a real‐time environment.